2012
DOI: 10.1002/lary.23362
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in children with postlingual hearing loss

Abstract: Children with well-developed language abilities before CI showed substantial (and statistically significant) early improvements in open-set speech perception abilities following implantation that continued beyond 2 years of follow-up. These results suggest that postlingual children are excellent candidates for CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…The PB-k lists are composed of 25 words found in average vocabulary of a kindergarten-aged child and is scored as ‘percent correct’ [35–37]. Pediatric CI recipients may continue improving in their speech perception performance for longer than 5 years after implantation [38]. However, for the purposes of this study, we used the PB-k scores that were part of a stable of performance as indicated by PB-k scores within 10 points of each other during two consecutive testing sessions, collected after at least 1 year of CI use.…”
Section: Methodsmentioning
confidence: 99%
“…The PB-k lists are composed of 25 words found in average vocabulary of a kindergarten-aged child and is scored as ‘percent correct’ [35–37]. Pediatric CI recipients may continue improving in their speech perception performance for longer than 5 years after implantation [38]. However, for the purposes of this study, we used the PB-k scores that were part of a stable of performance as indicated by PB-k scores within 10 points of each other during two consecutive testing sessions, collected after at least 1 year of CI use.…”
Section: Methodsmentioning
confidence: 99%
“…Clear distinction was made in the statistical analysis of data between children with congenital/ early onset (pre-lingual) hearing loss and children with post-natal (sudden/progressive) onset hearing loss. This distinction is important when a heterogeneous caseload is considered, since it is expected that children with postlingual onset hearing loss will mostly perform well after cochlear implantation as a result of more mature auditory pathways and early foundations for speech and language [24,[67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Children (referred to as ‘patients’), may receive any brand of regulatory approved implantable hearing device including any type of cochlear, bone conduction, electroacoustic or other implantable hearing device. If required, the Cochlear P-IROS platform also permits the capture of data from patients implanted at age 10 years or above, to address the growing trend for intervention in older children with an acquired or progressive hearing loss [ 30 ]. Additional questionnaires appropriate for this age bracket have been included for completion by these individuals' proxies.…”
Section: Methodsmentioning
confidence: 99%